The COVID-19 Pandemic and the Transformation of Health Policy: A Syndemic Perspective - Xi Chen; Annie Fan (Global Labor Organization (GLO), 2021)
The Coronavirus Disease 2019 (COVID-19) pandemic is bringing about once-in-a-century changes to human society. Three key properties escalate the COVID-19 pandemic into a syndemic. To address this triple crisis, we discuss the importance of integrating early, targeted and coordinated public health measures with more equitable social policy, and with health care policy that realigns incentives of the major players in the health care market. Drawing on evidence from past and present epidemics as well as comparing variations in response to the current health emergency between China, the U.S. and beyond, we navigate long-awaited health policy transformation in areas that help us better prepare for the next pandemic.
Keywords: I18; J24; H12; P41; H51; 330; COVID-19; pandemic; syndemic; healthcare reform; global health policy